Nykristne, Conversos, Marranos, judaister og Anusim I-II - Skovmand, Keld (Nordisk judaistik/Scandinavian Jewish Studies, 1994)
The first part of this article aims at presenting the two ways historians traditionally have dealt with the Converso problem – that is, the problem concerning the religious status of the Spanish Jews who converted to Christianity in the 14th and 15th centuries and their descendants.  The conventional view claims that the vast majority, if not all, of the conversos were not sincere converts because Christianity was forced upon them. These forced converts or anusim, it is claimed, brought up their children in their ancestral Jewish faith despite the fact that they lived in a society which was very hostile to Jews. They were subject to persecution by the Spanish Inquisition, which, according to this view, was established in order to eradicate secret Judaism. Consequently Jews continued to lead an underground existence in Spain centuries after the expulsion of 1492 until Crypto-Judaism gradually vanished as a result of diminishing contact with authentic Judaism. The alternative view claims that it was only a small minority of the Conversos, perhaps less than 5 per cent, who did not integrate into Christian Spanish society in the course of two or three generations. Consequently secret Judaism had ceased to be a problem at the time of the establishment of the Inquisition and is therefore to be considered a mere pretext and not the real cause for establishing this infamous institution.